The mechanism of branched-chain amino acid transferases in different diseases: Research progress and future prospects - Nong, Xiazhen; Zhang, Caiyun; Wang, Junmin; Ding, Peilun; Ji, Guang; Wu, Tao (Frontiers in Oncology, 2022)
It is well known that the enzyme catalyzes the first step of branched-chain amino acid (BCAA) catabolism is branched-chain amino transferase (BCAT), which is involved in the synthesis and degradation of leucine, isoleucine and valine. There are two main subtypes of human branched chain amino transferase (hBCAT), including cytoplasmic BCAT (BCAT1) and mitochondrial BCAT (BCAT2). In recent years, the role of BCAT in tumors has attracted the attention of scientists, and there have been continuous research reports that BCAT plays a role in the tumor, Alzheimer's disease, myeloid leukaemia and other diseases. It plays a significant role in the growth and development of diseases, and new discoveries about this gene in some diseases are made every year. BCAT usually promotes cancer proliferation and invasion by activating the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin pathway and activating Wnt/β-catenin signal transduction. This article reviews the role and mechanism of BCAT in different diseases, as well as the recent biomedical research progress. This review aims to make a comprehensive summary of the role and mechanism of BCAT in different diseases and to provide new research ideas for the treatment, prognosis and prevention of certain diseases.